O Direito entre a lei e a liberdade: uma dissertação sobre o probabilismo jurídico - Aires, Pedro França (2021)
This dissertation is an introduction to Legal Probabilism, a branch of theologicalmoral thought that was influential in the Iberian Peninsula and in Spanish America, between the 16th and 18th centuries. Its main objective is to depart from the concerns of contemporary Theory of Law (in particular, the analysis of the consequences of judicial decisions) and demonstrate how they were already present in another historical period. Therefore, the first chapter addresses the current challenges of law, in a historical perspective, drawing on the notion of post-modernity. In the second chapter, the cultural context of the Great Discoveries is outlined, with emphasis on the project that the Iberians traced for themselves, which contributed to the emergence of Legal Probabilism. The third chapter explains how, in the Moral Theology of the 16th-18th centuries, concerned with the solution of cases of conscience, Moral Probabilism emerged, which gave rise to Legal Probabilism. The fourth chapter organizes the main elements of Legal Probabilism, in the light of three of its most accessible authors, Bartolomé de Medina, Francisco Suarez and Juan de Caramuel y Lobkowitz, and some concrete cases, in order to characterize it as a thought marked by the notions of prognosis, circumstance and prudence. In the fifth chapter, postpositivist consequentialism and Legal Probabilism are compared, with regard to how these two currents of thought approach the effects arising from judicial decisions. In the sixth and final chapter, some suggestions are made on how this research could be further developed in the future